PERLINDUNGAN HUKUM TERKAIT EKPRESI BUDAYA TRADISIONAL “LAGU TRADISIONAL ACEH” DALAM BINGKAI HAK CIPTA - Nugraha, Tyas Adi Putra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Traditional Cultural Expression is an intellectual work that needs to be protected. Traditional Cultural Expression is rooted in three words: tradition, culture, and expression. The meaning of